2016
DOI: 10.1177/0308518x16633471
|View full text |Cite
|
Sign up to set email alerts
|

Harmonising devolved responsibility for biosecurity governance: The challenge of competing institutional logics

Abstract: Harmonisation of disease management practices across global space and the devolution of responsibility to a broader range of actors are two increasingly important approaches for ordering biosecurity governance. While these forms of ordering have been examined individually, the social science biosecurity literature provides limited insights into how they interact and interfere with one another, and the consequences for biosecurity implementation. This paper draws upon an institutional logics approach to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 53 publications
0
67
0
Order By: Relevance
“…(), this study found that such views are reflective of an agrarian institutional logic in which governments are argued to have a ‘moral responsibility to support farmers and family farming’ (Higgins et al . , p. 1143). Despite biosecurity being viewed as a government responsibility, farmers also questioned the capacity of governments to address biosecurity threats in the event of an outbreak, a contradiction identified also by Heffernan et al .…”
Section: On‐farm Implementation Of Biosecurity: the Challenges Of Devmentioning
confidence: 93%
See 3 more Smart Citations
“…(), this study found that such views are reflective of an agrarian institutional logic in which governments are argued to have a ‘moral responsibility to support farmers and family farming’ (Higgins et al . , p. 1143). Despite biosecurity being viewed as a government responsibility, farmers also questioned the capacity of governments to address biosecurity threats in the event of an outbreak, a contradiction identified also by Heffernan et al .…”
Section: On‐farm Implementation Of Biosecurity: the Challenges Of Devmentioning
confidence: 93%
“…A more recent study by Higgins et al . (), also found that producers attribute responsibility for biosecurity to external agents, and particularly government. Building on the work of Heffernan et al .…”
Section: On‐farm Implementation Of Biosecurity: the Challenges Of Devmentioning
confidence: 95%
See 2 more Smart Citations
“…Recognising geographical differences in terms of farmer perceptions of bTB risk is important if we think about the wider ‘institutional logic’ that drives market-based instruments (Higgins and others 2016). This logic is essentially a neoliberal agenda that encourages farmers to take more responsibility and to share some of the cost to control bTB through market-incentivised schemes (Maye and others 2014, Enticott 2016).…”
mentioning
confidence: 99%